TINJAUAN YURIDIS INDIKASI GEOGRAFIS SEBAGAI HAK KEKAYAAN INTELEKTUAL NON-INDIVIDUAL (KOMUNAL) - Dara Quthni Effida (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2019)
Industrial Revolution Era 4.0. requires us to continue to innovate, this innovation is something that is expensive and must be protected. One step to protect innovation is the protection of Intellectual Property Rights (IPR). Geographical Indications as one form of Intellectual Property Rights that has economic value, so it needs to get legal protection. This research is a qualitative research using Normative Juridical Approach.Geographical Indication is a sign that shows the area of origin of goods and / or products which due to geographical environmental factors including natural factors, human factors, or a combination of the two factors, give a certain reputation, quality and characteristics to the goods and / or products produced. To get protection for geographical indications, you need to request protection from the Minister. The concept of protection against geographical indications is communal protection, therefore applicants for geographical indications can come from the elements of: (1) Institutions that represent the public in a particular geographical area that is commercializing an item and / or product in the form of: a. natural resources; b. handicraft items; or c. industrial output. (2) Provincial or district / city regional governments.Keywords: Legal Protection, Geographical Indications, Communal.